2010
DOI: 10.1108/08876041011072573
|View full text |Cite
|
Sign up to set email alerts
|

Spirals of distrust vs spirals of trust in retail customer service: consumers as victims or allies

Abstract: PurposeThe purpose of this paper is to examine “nasty” retail shopping experiences. The paper aims to consider implications of distrust related to theft control measures in retail customer service.Design/methodology/approachStorytelling as a “memory‐work” method draws on phenomenology, hermeneutics, and the narrative. Researchers and participants worked together as co‐researchers to analyze and interpret “lived” experiences contained in their written personal stories. The authors extend this understanding in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 44 publications
(62 reference statements)
0
13
1
1
Order By: Relevance
“…The emotions of customers who experience poor treatment in retail stores have been described as mirroring those of crime victims. Among those feelings are anger, anxiety, confusion, helplessness, and shame (Chebat & Slusarczyk, 2005;Friend, Costley, & Brown, 2009;Gabbidon et al, 2008;). In addition, the experience of CRP can negatively affect an individual's self-worth (Gabbidon et al, 2008).…”
Section: Consumer Discriminationmentioning
confidence: 97%
“…The emotions of customers who experience poor treatment in retail stores have been described as mirroring those of crime victims. Among those feelings are anger, anxiety, confusion, helplessness, and shame (Chebat & Slusarczyk, 2005;Friend, Costley, & Brown, 2009;Gabbidon et al, 2008;). In addition, the experience of CRP can negatively affect an individual's self-worth (Gabbidon et al, 2008).…”
Section: Consumer Discriminationmentioning
confidence: 97%
“…Wang and Huff (2007) corroborate this finding, particularly among customers in the early stages of trust development. Friend, Costley, and Brown (2010), through qualitative research, found that WOM can be used by customers to spread their feelings of distrust regarding a particular company. It is therefore possible that when someone feels distrust, he/she can spread negative information about the company to influence other customers' behavior.…”
Section: Antecedents Of Negative Wommentioning
confidence: 99%
“…The multiple studies on trust repair have attracted considerable attention regarding competence or integrity-based trust violations, including public-organization or stakeholder-company relationships [19,20], interpersonal or organizational relationships [21,22], contractors-subcontractors relationships [17], citizen-government relationships [23], and buyer-vendor relationships in traditional or online environment [13,24]. Indeed, trust decline encompasses both a single violation event with a sharp destruction of trust and gradual trust erosion with time [25].…”
Section: Trust Decline: Sharp Violation and Gradual Erosionmentioning
confidence: 99%
“…The specific type and its nature of trust influence its repairing emphasis. In buyerseller relationships, current trust repair studies rarely consider the nature of a calculusbased trust by regarding that the single relational or affective strategy (such as apologies, denials or excuses) is effective [12,13], or that the affective and tangible strategy (such as financial compensation) are equally effective in trust repairing [14,15]. Our work bridges the existing research gap by identifying the nature of trust in m-commerce buyer-seller relationship and answers the following research questions are: Do consumers re-trust in benefits, emotions or both?…”
Section: Introductionmentioning
confidence: 99%